Micosis Fungoide Intersticial: Diagnóstico diferencial con el Granuloma Anular Intersticial Interstitial Mycosis Fungoides: Differential diagnosis with Interstitial Granuloma Annulare - RE Achenbach; LJA Lococo; GF Sánchez; S Monroy; MI Jorge; EH Pittaro (Asociación Argentina de Dermatología, 2011)
La micosis fungoide en su variante histopatológica intersticial, puede ser confundida con el granuloma anular intersticial. Se ejemplifican dos casos de micosis fungoide intersticial y se subrayan los criterios histopatológicos para el diagnóstico diferencial, entre estas dos entidades. The interstitial type of mycosis fungoides and the interstitial type of granuloma annulare have several findings in common, in some cases may be difficult to differentiate them. Two cases of interstitial mycosis fungoides are presented and the histopathological features for the differential diagnosis are discussed.